Virtual FSKTM / Chuah Hai Ping - Chuah, Hai Ping (2002)
Nowadays, client-server systems are one of the popular systems architecture to be built up either through the network or the Internet. Through client-server systems, users can be added and monitored by the system administrator and users can access as well as exchange data through the particular client-server system. This will bring lots of benefits to them. As my faculty, FSKTM is going to merge into electronics system; every fields of the faculty system will be changed into the electronic system. With the virtual FSKTM for distance learning, all the properties and methods of the distance learning will be merged into this new electronic system. All the distance just need to connect to the internet and straight away can access to the website for their online learning. I had decided to develop an online virtual faculty system for distance learning, which is a client-server based system. Through this online virtual faculty system, user will be able to learn or study through the FSKTM 's website. All that the client needs to do is to connect to our centralized server for exchange and updating of data. However, this client-server system does not involve online transactions. All the students need to pay before they can access to this website for their study. Every field of distance learning will be run through the system except for the final exam part. All the students need to come to the university to sit for the exam or go to a learning center to take the exam. All the students can download the complete notes of course they have registered for each semester contact with the lecturers using various methods and etc.